Correlation of Solar Activity and Interplanetary Parameters on Cosmic rays Intensity Investigated through Multivariate Analysis from 1964 to 2020 - Putri, Annisa Novia Indra; Herdiwijaya, Dhani (Journal of Multidisciplinary Applied Natural Science, 2026)
This study investigated the relationship between the most influential solar and interplanetary plasma parameters and cosmic ray modulation. A principal component analysis (PCA) method was used. The variations of the cosmic ray intensity were obtained at 6 different locations with different latitudes and cutoff rigidities. These stations were located at mid- to high latitudes (SOPO, OULU, and NEWK), while the remaining three were located at low latitudes (MXCO, TSMB, and PSNM). A parameter ranking based on PCA confirmed that sunspot number, interplanetary magnetic field (IMF) magnitude, heliospheric current sheet (HCS) tilt, halo coronal mass ejection (CME) velocity, Bz, and proton density have the highest link with the modulation of cosmic ray intensity. Meanwhile, the PCA analysis at low latitudes revealed that the cone angle and the magnetic field components By and Bx along the y- and x-axes, the mean magnetic field of the Sun, the HCS tilt, and the IMF magnitude exert the greatest correlation on the cosmic ray intensity modulation at this station. The correlation between the analyzed parameters and cosmic ray modulation appears to vary with latitude.